ANALYSIS OF STRATEGIC GOALS AND INTERMEDIATE RESULTS OF EDUCATIONAL ORGANIZATIONS RESTRUCTURING IN THE FIELD OF RUSSIAN HIGHER EDUCATION - O. Kirillova; V. Nikulin (Вестник университета, 2016)
The article is devoted to peculiarities of restructuring process in the educational organizations that work in the sphere of higher education in Russia. Strategic goals of higher education sphere development are analyzed. Some results of restructuring of largest Russian universities are summarized and renewed set of management principles for educational organization based on corporate citizenship approach is proposed.